DIGITAL MARKETING IN PROMOTING EVENTS AND FESTIVITIES. A CASE OF SANUR VILLAGE FESTIVAL - I Gusti Ayu Oka Suryawardani; Agung Suryawan Wiranatha (Institut Pariwisata dan Bisnis Internasional, 2016)
Digital marketing intends to influence consumers’ desire, cognition, feelings, belief, attitude and image concerning products and brands which has the ultimate goal to influence consumers’ purchase behaviour. Digital marketing has been widely used to promote tourism around the world, including Sanur Village Festival in Bali. Sanur Village Festival is one of the famous events in Bali which has been held annually since year 2005 in order to recover image and reputation of Bali as a peaceful destination after terrorism attacks. Research was designed to examine the role of digital marketing in visitors’ behavioural intention in visiting Sanur Village Festival 2015. Research was undertaken in the area of Sanur Village Festival (SVF) on 26 - 30 August 2015. The number of respondents was 207 visitors. Data was analysed by using SmartPLS program.The results show that among four indicators, only indicator of event advertisement significantly influences visitors’ intention in visiting SVF with Alpha Cronbach coefficient is 0.59 (≥ 0.6) and correlation coefficient is 0.369 (≥ 0.3). Meanwhile, three other indicators, namely source of event’s information, accompany to visit, and event’s arrangement is not significant to influence visitors’ intention to visit SVF. Among types of advertisement, the results show that the highest percentage of advertisement’s type which affected the visitors’ intention to visit SVF is the use of digital advertisement, namely television (41.2%), internet (32.7%), and broadcast (13.4%). However, non-digital advertisement has less influence, namely printed media (4.8%), banner (4.5%) and brochure (3.4%). Understanding development of preferred weblogs and portals by internet users is very important to be able to get more success in gaining specific target market, as people are getting more internets oriented. The results indicate that successful promotional strategy in the information and technological era should be focused on digital marketing with a clear focus on efficiency, sustainability and experiences enrichment. However, it cannot be denied that other factors such as attitudes toward behaviour and perceived behaviour control are also defining factors in influencing consumers’ purchase behaviour which is also need to be focused on.